Interaction of participants of urban freight consolidation of different levels - Savchenko, Lidiia; Polishchuk, Volodymyr; Grygorak, Mariya (Management and Entrepreneurship: Trends of Development, 2019)
The purpose of this publication is generalization of research on the types of urban consolidation, classification of systems for urban freight consolidation by levels, consideration of participants at each level and schemes of their interaction, as well as analysis of direct and reverse flows that accompany this interaction. The works of domestic and foreign scientists on the problems of urban freight transportation and use of consolidation for their solving are the theoretical and methodological basis of the research. Data of official statistical and analytical materials of ministries and departments of Ukraine and world agencies made up the Information basis. When solving the tasks set, methods of economic analysis, systematization, generalization, comparison were applied. The results of the work are classifications of consolidation schemes for urban distribution, urban consolidation centers and their participants. Different levels of urban consolidation allow flexible application of the idea of consolidation to cities of various sizes and topologies, while reducing congestion and improving environmental situation in the city. The forward and reverse flows between various participants in the urban distribution system are evaluated. The prospect of the study is to consider the schemes of consolidation of different levels and an assessment of their economic and socio-ecological efficiency. The limitations of the results obtained are their applicability exclusively for urban areas and for consolidated transportation between cities. The presence of all levels of freight consolidation can be economically feasible only for cities with population of over 1 million inhabitants with corresponding long delivery distances. The practical significance of the study lies in the possibility of using the proposed classification and schemes of direct and reverse flows in the design of urban distribution schemes with the involvement of consolidation centers at various levels.JEL Classification: R40, R22, O18.https://doi.org/10.26661/2522-1566/2019-3/09-07